Businesses Have Human Rights, Too - Butler, Petra (Victoria University of Wellington Law Review, 2019)
This article is a verbatim reproduction of my professorial inaugural lecture, delivered on 23 July 2019. The lecture included visual images and an audio recording that cannot be reproduced here.